KAJIAN HUKUM ATAS PERNYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL SECARA KONSILIASI - Rumelda Silalahi (JURNAL DARMA AGUNG, 2019)
This research aims at finding legal studies on conciliation settlement of industrial relations. The method used in this study is sociological juridical, in which the researcher examines based on legislation that regulates the problem by looking directly at the implementation and application of these regulations in practice. Method of data analysis used is analytical descriptive. The research finding shows that in the process of dispute resolution by way of conciliation a new conciliation institution works after the parties submit a written settlement request to the conciliator appointed and agreed by both parties, and the dispute concerning rights, cannot be submitted through this conciliation institution. The conciliator's verdict in the settlement of industrial relations is binding. The conciliation settlement resolves industrial disputes through deliberation, but if conciliation is not reached it will issue a suggestion concluding the conciliator's opinion of the dispute faced by him. Parties who feel disadvantaged for such a proposal have the right to refuse to carry out the content of the lawsuit to the court to the Industrial Relations Court (pursuant to Article 23 paragraph 2 of the Act No. 2 of 2004).